(untitled) (Research, Society and Development, 2023)
The World Health Organization (WHO) reported that the worldwide prevalence of obesity has nearly tripled since 1975, and 13% of adults aged ≥18 years were obese in 2016. At the same time, global diets have changed markedly from traditional meal-based diets freshly prepared for modern diets made up of large amounts of packaged and processed foods. The objective of this study was to carry out an integrative literature review in order to synthesize information about the impact of consumption of ultra-processed foods on the increased risk of overweight. This is an integrative literature review built according to the following steps: elaboration of the guiding question, search or sampling in the literature, data collection, critical analysis of the included studies, discussion of the results and presentation of the integrative review. After the eligibility/critical evaluation of the full texts of 24 records, 6 met the inclusion criteria and proceeded to the data extraction, exhaustive reading and knowledge synthesis phase. The studies explained here suggest that the consumption of ultra-processed foods increases the risk of overweight and obesity in populations from different geographic locations, emphasizing the need to increase policies to control these comorbidities, mainly through strategies focused on food and nutrition.